European eel (Anguilla anguilla L.) metallothionein, endocrine, metabolic and genotoxic responses to copper exposure - Oliveira, M. (2020)
This study investigated Anguilla anguilla (European eel) physiological and genotoxic responses to copper (Cu) and their relation with metallothionein (MT) protection. Eels were exposed during 7 days to Cu 0.2 micromol/L. MT induction was assessed in gill and liver, revealing significant response only in liver. Endocrine responses displayed a plasma free triiodothyronine (T3) and cortisol significant decrease, though the thyroid-stimulating hormone (TSH) and free thyroxine (T4) concentrations were unaltered. A significant plasma glucose increase was observed whereas lactate was significantly decreased. Despite the absence of DNA integrity decrease in blood, gill, liver and kidney, erythrocytic nuclear abnormalities (ENA) frequency significantly increased in Cu exposed group. MT induction was insufficient to prevent endocrine and metabolic alterations as well as genotoxicity/clastogenicity in blood. However, MT protection was evident in liver by preventing DNA integrity loss. Globally, it was demonstrated that Cu environmentally realistic levels may pose a serious ecological risk to fish.